Hazard identification and risk assessment of biogas plant with proton exchange membrane fuel cell technology - Masli Irwan Rosli; Ahmad Faris Mohd Fekeri; Dyg Siti Nurzailyn Abg Shamsuddin; Ikhmal Zariq Al Imran Jamal Ikhsan; Izan Shukrizal Shukor; Mohd Hafizuddin Muhamad; Nur Ain Nadhirah Mohamad Razali (Penerbit Universiti Kebangsaan Malaysia, 2024)
Biogas-fed proton exchange membrane fuel cell (PEMFC) plants offer a sustainable energy solution, but their operation can pose significant hazards and risks. Ensuring the safety of these plants is paramount, especially given the potential for fires, explosions, and chemical exposures. This study evaluated hazards and risks in biogas-fed proton exchange membrane fuel cell (PEMFC) plants using six analytical methods: Dow’s fire and explosion index (FEI), Dow’s chemical expo-sure index (CEI), Hazard and Operability Study (HAZOP), Risk Matrix Analysis (RMA), Bayesian Network (BN) and ALOHA® software hazard modelling. The FEI analysis revealed that the anaerobic digester and bio-gas storage tank exhibited severe hazards (FEI =170), thereby signifying the highest risks within the plant. CEI analysis revealed the spread of the highest hydrogen sulfide (H2 S) concentration up to 129 meters from the anaerobic digester and storage tank location. Further assessment was conducted, calculating risk values using the RMA and performing additional HAZOP analysis specifically for these units. The results confirmed similar risk levels (4-20) between the units, except for a higher explosion risk in the storage tank. The novelty of this research lies in the application of Bayesian Network (BN) analysis. In addition to assessing the hazards associated with PEMFC, our BN analysis reveals that the risk of fire attributed to PEMFC ranges between 10% and 18%, while the risk of explosion falls within the range of 3% to 17%. Based on the hierarchy control concept, several effective mitigation controls were proposed to enhance the safety of biogas-fed PEMFC plants. In future research, a deeper exploration of human error and equipment malfunctions within hazard modelling is crucial for a more precise hazard assessment.